A FIELD TEST OF δ13C AS A TRACER OF AEROBIC HYDROCARBON DEGRADATION - Bugna G.C.; Chanton J.P.; Kelley C.A.; Stauffer T.B.; MacIntyre W.G.; Libelo E.L. (My University, 2004)
The controlled release of a mixture simulating jet fuel was conducted to determine the effects of transport and degradation on the δ13C of reactants and products in a field setting. Benzene, toluene, naphthalene, xylenes, and decane were mixed with native soil and placed 4 m below ground into a surficial aquifer. The δ13C values of the hydrocarbons prior to and after emplacement were measured and no significant isotopic fractionation was observed following migration and partial degradation. The δ13C values of the compounds within the hydrocarbon mixture prior to addition and following 40 and 164 days in the field ranged from -26.6 to -30.0, -26.3 to -30.4 and -26.5 to -29.4%%, respectively. Also measured were the concentrations and δ13C values of respiration endproducts CO2 and CH4 in groundwater samples prior to and 164, 278, 468, 642 and 831 days after the contamination of the surficial aquifer. Endproduct concentrations were clearly elevated relative to pre-emplacement values indicating microbial respiration of the added hydrocarbon mixture. Isotope mass balance calculations yielded similar δ13C values for the sum of the respiration products and the added hydrocarbon mixture. Our results indicate that the products of hydrocarbon respiration reflect the δ13C of the substrates, and in less controlled contaminated field settings DIC isotopic values may be useful for estimating hydrocarbon degradation when DIC up-gradient of the spill has a δ13C value different from that of the contaminants.